Determinants of vulva hygiene practices and their association with abnormal vaginal discharge among adolescent girls - Riana Rosa; Asparian Asparian; Herwansyah Herwansyah; Sri Astuti Siregar (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Vaginal discharge is one of the common reproductive health problems experienced by adolescent girls and may be influenced by poor vulva hygiene practices. Several factors are presumed to be related to vulva hygiene practices and vaginal discharge, including knowledge, attitude, action, facilities, exposure to reproductive health information, family support, peer support, and teacher support. This study aimed to identify the determinants of vulva hygiene practices related to vaginal discharge among adolescent girls  at Madrasah Aliyah Negeri 2 Kota Jambi. Purpose: To identify the determinants of vulva hygiene practices and examine their association with the incidence of abnormal vaginal discharge  among adolescent girls. Method: A quantitative study using an analytical observational approach with a cross-sectional design was conducted in April 2026. The study population comprised all 253 eleventh-grade female students at MAN 2 Kota Jambi, with a sample size of 156 respondents selected via Proportional Random Sampling based on inclusion criteria. Primary data were gathered online via Google Form questionnaires and analyzed using univariate and bivariate statistical tests (Chi-Square, α = 0.05). Results: Univariate analysis showed that 58.3% of respondents experienced abnormal vaginal discharge. Most respondents possessed good knowledge (80.8%), positive attitudes (60.3%), good vulva hygiene practices (50.6%), adequate facilities (58.3%), high exposure to reproductive health information (63.5%), family support (56.4%), peer support (58.3%), and teacher support (64.7%). Bivariate analysis revealed that factors significantly associated with vulva hygiene practices were the availability of sanitation facilities  (p=0.021), family support (p=0.015), peer support (p=0.000), and teacher support (p=0.039), while knowledge (p=0.743), attitude (p=0.844), and exposure to reproductive health information (p=0.774) showed no significant association. Furthermore, a significant correlation was found between vulva hygiene practices and the incidence of vaginal discharge (p=0.004; PR=1.697; 95% CI=1.169-2.462), indicating that adolescents with poor vulva hygiene practices have a 1.697 times higher risk of experiencing abnormal vaginal discharge. Conclusion: Vulva hygiene practices among adolescent girls  are significantly influenced by enabling factors (facilities) and reinforcing factors (family, peer, and teacher support). Inadequate vulva hygiene practices are proven to significantly increase the risk of abnormal vaginal discharge. Reproductive health promotion programs in schools are recommended to optimize sanitation facilities and strengthen social support networks to encourage proper hygiene habits.